Early High School Graduation: Policy Support for Secondary Acceleration. Issue 3 (July 2022) - Plucker, Jonathan A.; Healey, Grace; Meyer, Melanie S.; Roberts, Julia L.
In recent years, state and local support for academic acceleration has created opportunities for students with advanced learning needs to move through their education at a pace that matches their abilities and may be faster than their same-age peers. As a result, it is not uncommon for exceptionally bright students to complete their high school graduation requirements early. These students have the option to stay in high school and complete additional coursework or move on to postsecondary settings to continue their academic talent development. This article explores state and local policies on early graduation and highlights supportive policies and potential barriers to this type of acceleration.